(untitled) (Bangladesh Journal of Urology, 2020)
More than 90% of malignant renal tumors encountered in children are Nephroblastoma. Renal Cell Carcinoma is extremely rare in children but in children older than 5 years with renal masses it is very important to suspect diagnosis. We present a 6 years old child primarily presented with abdominal mass and haematuria. The mass was described by ultrasonography & computer tomography as Wilms’ Tumour which is commonest before 5 years of age with peak age of presentation is 3 years of life. Surgery is the best treatment and prognosis is favorable when tumour is localized and completely eradicated. In our case no adjuvant therapy was given nephrectomy Bangladesh Journal of Urology, Vol. 20, No. 2, July 2017 p.102-104